Pelatihan dan Pendampingan Pembelajaran STEM-PjBL dengan Media Pembelajaran Edukit - Ana Rokhmawati; Lukman Jakfar Shodiq; Naily Rizqi Amaliyah (BADAN PENERBIT STIEPARI PRESS, 2025)
STEM learning is highly engaging, but many high school biology teachers in Lumajang Regency are still confused about how to implement it in biology lessons. The goal of this community service project is to expand the understanding of concepts and enhance the skills of high school biology teachers in designing STEM-PjBL (Project-based Learning) lessons. The project consists of three stages: preparation, implementation, and evaluation. In the preparation stage, field surveys and coordination with partners were conducted. In the implementation stage, materials on STEM-PjBL were provided, followed by hands-on practice in developing teaching tools and interactive discussions. In the evaluation stage, pre-tests and post-tests were used to assess participants' knowledge. The analysis of pre-test and post-test results showed a 2.29% increase in the knowledge of biology teachers in Lumajang Regency about STEM-PjBL learning. While the teachers' knowledge was quite good, they still need a deeper understanding of the application of STEM-PjBL. Additionally, this community service resulted in the development of educational media, such as a biocomposter edukit and aquaponic edukit, which can be sustainably used for school-based learning activities.